Analisis Perbedaan Perbankan Syariah Dengan Perbankan Konvensional - Nanang Sobarna (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2021)
Islamic banking is a financial institution that has a very important role in advancing the Indonesian economy as well as responding to the community's need to use a banking system based on sharia principles. However, sometimes there are many perceptions that Islamic banking is the same as conventional banking. Islamic banking has fundamental differences with conventional banking, namely regarding legal aspects, organizational structure, financed business activities and work environment. Sharia banking operations are based on sharia principles, namely the principle of profit sharing, the principle of buying and selling and leasing by running a business through mudharabah, musyarokah, murabbahah and ijaroh contracts. While conventional banking provides services in payment traffic with the principle of setting interest for both deposit and loan products (credit) and applying various fees in the form of nominal and certain percentages.